Association of change in the neighborhood obesogenic environment with colorectal cancer risk: The Multiethnic Cohort Study. (April 2020) - Shvetsov, Yurii B.; Shariff-Marco, Salma; Yang, Juan; Conroy, Shannon M.; Canchola, Alison J.; Albright, Cheryl L.; Park, Song-Yi; Monroe, Kristine R.; Le Marchand, Loïc; Gomez, Scarlett Lin; Wilkens, Lynne R.; Cheng, Iona
Abstract: Background: Neighborhood environment has been associated with health behaviors. Despite the evidence of the influence of neighborhood social and physical factors on cancer risk, no research has evaluated whether changes in the neighborhood obesogenic environment, either by physical moves to different neighborhoods or experiencing neighborhood redevelopment or neglect, affect cancer risk. Methods: The association of change in neighborhood environment attributes (socioeconomic status, population density, restaurant and retail food environments, numbers of recreational facilities and businesses, commute patterns, traffic density, and street connectivity) with colorectal cancer (CRC) risk was examined among 95, 472 Los Angeles, CA, Multiethnic Cohort participants, including 2295 invasive CRC cases diagnosed between 1993 and 2010 using Cox proportional hazards regression, adjusting for age, race/ethnicity, other risk factors including BMI and physical activity, and baseline levels of neighborhood attributes. Stratified analyses were conducted by racial/ethnic group and moving status. Results: 40% of participants moved (changed physical residence) during follow-up. Across all races/ethnicities, upward change in population density was statistically significantly associated with higher CRC risk among male and female non-movers (HR: 1.35 and 1.41, respectively). The same association was also observed separately among female African American and Japanese American non-movers, male Latino non-movers, female African American and male White movers. Downward change in population density was significantly related to higher CRC risk among female non-movers (HR: 1.33). Downward change in traffic density was associated with lower CRC risk among male non-movers but with higher CRC risk among female movers (HR: 0.66 and 1.43, respectively). Downward changes in street connectivity or the number of recreational facilities were associated with higher CRC risk (HR: 1.34 and 1.54, respectively). Upward change in the number of recreational facilities was associated with lower CRC risk among female non-movers (HR: 0.70). Changes in the other neighborhood attributes did not exhibit significant associations with CRC risk within more than one racial/ethnic group. Conclusion: Changes over time in neighborhood attributes have an effect on the risk of colorectal cancer, which is separate from the baseline levels of the same attributes and individual-level risk factors, and differs between sexes, movers and non-movers and across racial/ethnic groups. Highlights: A person's neighborhood environment can change due to physical moves or neighborhood redevelopment. Association of change in neighborhood environment with colorectal cancer risk was examined. The California part of the Multiethnic Cohort was used for the analysis. Upward change in population density was associated with higher colorectal cancer risk among non-movers.